ANALISIS KEPUASAN NASABAH TABUNGAN PADA PT. BANK RAKYAT INDONESIA (PERSERO) CABANG CILACAP - Amin Budiarti; Farida Jazarianti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2010)
The aims of this research at examining the customer satisfaction. Those influencing are interest rate, teller sevice, waiting room facilities, service process and price. Population in this research are all customer of saving accounts in Cilacap Branch Office PT Bank Rakyat Indonesia, a sample of 100 respondents is determined by employing simple ramdom sampling method. The Fishbein Extended is used to analyse the data which calculates individual attitude upon behavior based on evaluation subjective on norm and behavior intention. The result of the research are: the customer of saving accounts consider the interest rate, teller service, waiting room facilities, sevice facilities and price conform with customers’expectation.  All attribute is important while the interest rate is the most important attribute. Family and companion agree the customer have saving accounts, personal attitude is more dominant than the reference group opinion in deciding the behavior of saving and behavior intention of customer has positive attitude.Key words: customer satisfaction